Exploring the great outdoors: a bibliometric journey into adventure tourism - Mohamad@Alwi, Mohamad Khairi; Mohd Nazari, Norwani; Shahrin, Muhamad (UiTM Press, 2025)
Adventure tourism studies have garnered increasing attention from scholars worldwide, as reflected in numerous academic publication databases. Most existing research in this field relies on empirical studies conducted through surveys and interviews, with some contributions from conceptual papers. However, bibliometric analyses of adventure tourism remain largely underexplored. This study adopts a bibliometric analysis approach to provide a comprehensive overview of the landscape, evolution, and trends in adventure tourism research. Additionally, this method allows the identification of leading authors, institutions, and countries actively contributing to the field. The study also aims to generate visualization maps using VOSviewer software, illustrating the connections between authors, institutions, and keyword occurrences. A total of 661 scientific documents related to adventure tourism in various forms were sourced from the Elsevier Scopus database. Through this analysis, prominent authors, highly productive institutions, frequent keywords, top funders, and other significant metrics in the field were identified. Finally, this paper offers valuable insights for future researchers by highlighting critical research gaps through the examination of keyword occurrences associated with adventure tourism. In contrast to earlier reviews, this analysis identifies evolving research fronts and underexplored thematic areas, thereby offering a more dynamic and current perspective on the intellectual and structural development of the field.